Effects of Financial Management Practices on Performance of Small and Medium Enterprises - Samir Din (Uganda Christian University, 2023)
The study evaluated the effect of financial management practices like working capital management, capital structure management and fixed asset management on performance of a company. The study's main focus was on how financial management attributes such as working capital management, capital structure management and fixed asset management affected Coca-Cola Company’s financial performance. The research study utilized a descriptive research design. A sample of the study consisted of 35 respondents working in the company, related to different departments. The finance executives, administrators and financial analysts of the company responded to the questionnaire that was self-administered to collect data from the respondents. Purposive and random sampling techniques were used to determine the sample size. Data analysis was done using Statistical Package for Social Scientists (SPSS) version 20 software. Data was edited, coded, and tabulated using frequencies, ensuring completeness, accuracy, and uniformity. Frequency estimates were calculated, mean and standard deviation too, was displayed using frequency tabulation. The company was found to have put in place robust financial management practices in form of capital structure, working capital and fixed asset management which positively affected performance in line with profitability and could be presumed to be an integral management tool for the company. Recommendations were further made to refine the process of determining an optimal capital structure for a company, delicately balancing equity and debt financing while considering risk tolerance, cash flow stability, and cost of debt so as to minimize the weighted average cost of capital (WACC), leading to reduced financing expenses and increased shareholder value, and might involve strategic moves like debt refinancing or issuance, favorable supplier terms, boosting liquidity and diminishing reliance on external financing. Optimizing fixed asset utilization requires regular performance assessments considering factors such as depreciation and maintenance Long-term planning integrates these financial decisions with strategic goals, preventing short-sighted choices and fostering sustainable growth, with benchmarking against industry peers recommended to adopt successful practices for capital structure, working capital, and fixed asset management.
This is a dissertation.